Identifying Potential Biomarkers of Prognostic Value in Colorectal Cancer via Tumor Microenvironment Data Mining - Li, Lei; Du, Xiao; Fan, Guangyi (Frontiers in Genetics, 2022)
Colorectal cancer is a common cancer (CRC) that has increased rapidly worldwide in the past decades with a relatively high mortality rate. An increasing body of evidence has highlighted the importance of infiltrating immune and stromal cells in CRC. In this study, based on gene expression data of CRC patients in TCGA database we used the ESTIMATE algorithm to calculate the immune and stromal scores. Results showed there was potential correlation between these scores and the prognosis, and that patients with higher immune score and lower stromal score had longer survival time. We found that immune score was correlated with clinical characteristics including tumor location, tumor stage, and survival time. Specifically, the right-sided colon cancer had markedly elevated immune score, compared to left-sided colon cancer and rectal cancer. These results might be useful for understanding tumor microenvironment in colorectal cancer. Through the differential analysis we got a list of genes significantly associated with immune and stromal scores. Gene Set Enrichment and protein-protein interaction network analysis were used to further illustrate these differentially expressed genes. Finally, 15 hub genes were identified, and three (CXCL9, CXCL10 and SELL) of them were validated with favorable outcomes in CRC patients. Our result suggested that these tumor microenvironment related genes might be potential biomarkers for the prognosis of CRC.